Comparison of Malaysia's building regulations regarding means of escape routes in student hostel - Jaafar, Adnin Syaza; Abdul Talib, Yuhainis; Ismail, Asmat; Othman, Muhammad Anas (Universiti Teknologi MARA, Perak, 2025)
A student hostel is an accommodation provided by educational institutions, offering shared living spaces for students. It needs to comply with building standards and safety features. Fire incidents in a student hostel can negatively impact students' futures. Tragic instances, such as the fire at the Madrasah Darul Quran Ittifaqiyah in 2017 and a similar incident in Georgetown, Guyana, highlighted the importance of these safety measures. Due to this, the Twelfth Malaysia Plan mandates measures to address outdated and unsafe buildings, particularly student hostels. Buildings constructed based on outdated standards may not meet current requirements. Therefore, this research aims to identify the design criteria of means of escape and to evaluate the changes in Uniform Building By-Law provisions regarding means of escape. A qualitative approach is used for data collection via evaluating archival documents and expert validation. The building standards compared are the Uniform Building By-Laws 1984 as of 2015 and Uniform Building By-Laws 1984 as of 2022. The collected data is analysed using content analysis that integrates passive and active fire protection by distinguishing the means of escape requirements prescribed in both building regulations. The analysis identified seven design criteria for safe escape routes: travel distance, door, exit, staircase, emergency lighting, communication, power system, signage, and fire-fighting requirements. This research provides valuable insights for designers and policymakers by highlighting regulatory changes such as newly added, removed, substituted, amended, and maintained prescriptive requirements. By shedding light on the motivations behind these changes, this research could impact future updates to building laws.